2023
DOI: 10.1371/journal.pone.0282698
|View full text |Cite
|
Sign up to set email alerts
|

Extended reality as a training method for medical first responders in mass casualty incidents: A protocol for a systematic review

Abstract: Introduction/Background Mass-casualty incidents (MCIs) and disasters require an organised and effective response from medical first responders (MFRs). As such, novel training methods have emerged to prepare and adequately train MFRs for these challenging situations. Particular focus should be placed on extended reality (XR), which encompasses virtual, augmented and mixed reality (VR, AR, and MR, respectively), and allows participants to develop high-quality skills in realistic and immersive environments. Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Even so, the care of the deceased is often neglected in disaster planning. Major disasters in recent years, such as the 2010 Haiti earthquake or the 2016 Central Italy earthquakes, have shown that there is not enough guidance for first responders [17]. Immediately following a major disaster, residents from local communities are the first to deal with the retrieval of dead bodies, before forensic specialists are able to reach the site.…”
Section: Post-mortem Pavilionmentioning
confidence: 99%
“…Even so, the care of the deceased is often neglected in disaster planning. Major disasters in recent years, such as the 2010 Haiti earthquake or the 2016 Central Italy earthquakes, have shown that there is not enough guidance for first responders [17]. Immediately following a major disaster, residents from local communities are the first to deal with the retrieval of dead bodies, before forensic specialists are able to reach the site.…”
Section: Post-mortem Pavilionmentioning
confidence: 99%
“…Scalability refers to the fact that, unlike traditional simulation methods, which require significant hardware investment, VR can adapt to new procedures and scenarios with simple software iterations. This flexibility not only broadens educational possibilities but could also democratize access to high-quality medical training, especially in resource-limited countries [14,15].…”
Section: Introductionmentioning
confidence: 99%